2010
DOI: 10.1042/bj20100538
|View full text |Cite
|
Sign up to set email alerts
|

Human platelets express and are activated by galectin-8

Abstract: Gals (galectins) are proteins with glycan affinity that are emerging as mediators of atherosclerosis. Despite the similarities in structure and sequence, different Gals exert distinct effects on their target cells. We have shown that Gal-1 triggers platelet activation, suggesting a role for Gals in thrombus formation. Since Gal-8 is expressed upon endothelial activation and also contributes to inflammation, to understand further the role of these lectins in haemostasis, we evaluated the effect of Gal-8 on huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
100
0
11

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 76 publications
(117 citation statements)
references
References 40 publications
6
100
0
11
Order By: Relevance
“…We also determined that Gal-8's single N-CRD is sufficient to trigger platelet activation (31). In agreement, in this study we showed that Gal-1 costimulated T cells in the presence of the cognate peptide, but it was unable to trigger proliferation of naive splenocytes, even when tested at a high concentration (20 mM).…”
Section: Discussionsupporting
confidence: 75%
“…We also determined that Gal-8's single N-CRD is sufficient to trigger platelet activation (31). In agreement, in this study we showed that Gal-1 costimulated T cells in the presence of the cognate peptide, but it was unable to trigger proliferation of naive splenocytes, even when tested at a high concentration (20 mM).…”
Section: Discussionsupporting
confidence: 75%
“…Platelet activation mediated by galectin-1 or galectin-8 is prevented by lactose but not by sucrose indicating the interaction of these lectins with specific carbohydrate ligands on the platelet surface. MALDI/TOF mass spectrometry analyses determined that both galectins binds the subunit IIb from the IIbβ3 integrin (Pacienza, Pozner et al 2008;Romaniuk, Tribulatti et al 2010). Additionally, while galectin-8 also binds GPIb and V from GPIb-IX-V complex (Romaniuk, Tribulatti et al 2010), galectin-1 interacts with β1.…”
Section: Platelet Receptors For Galectin-1 and Galectinmentioning
confidence: 99%
“…Additionally, while galectin-8 also binds GPIb and V from GPIb-IX-V complex (Romaniuk, Tribulatti et al 2010), galectin-1 interacts with β1. However, the use of platelets derived from patients who are deficient in IIbβ3 or in GPIb, revealed that only GPIb and integrin IIbβ3 are essential for galectin-8-and 1 dependent signal transduction respectively, and therefore represent functional counter-receptors (Romaniuk, Tribulatti et al 2010;Romaniuk, Croci et al 2012). …”
Section: Platelet Receptors For Galectin-1 and Galectinmentioning
confidence: 99%
See 2 more Smart Citations